Sexual health knowledge among secondary school students in Morogoro, Tanzania: half full or full empty? - Kaale, Gloria; Muhanga, Mikidadi (International Journal of Health, 2017)
Background: Sexual health knowledge (SHK) is very crucial as the world is facing HIV/AIDS tragedy, increased cases of sexually transmitted infections (STIs) and unsafe abortions among adolescents. It is obvious that knowledge is an important prevention factor for any disease.Objectives: The study was conducted to assess knowledge and attitude on sexual health among secondary school students in Morogoro Municipality. Specifically the study (I: (i) examined students’ knowledge and attitude on sexual transmitted infections, (ii) analyzed student's awareness on early pregnancy prevention, and; (iii) determined students’ knowledge on issues related to puberty.Methods: The study involved 75 respondents from five secondary schools and 13 key informants through purposive sampling and simple random sampling techniques. Data were collected using a structured questionnaire. Data collected were analyzed using Statistical Package for Social Science (SPSS) ver.12.Results: Findings revealed that 79.8% of the respondents had knowledge on sexually transmitted infections, 86.5% were aware ofmethods of controlling early pregnancies; 83.9% have never used protective gears during sexual intercourses, and 54.7% did not understand a menstruation cycle.Conclusion: The study recommended for provision of sexual health knowledge to students to reduce incidences of early pregnancies and sexually transmitted infections; likewise on the need to use protective gears during sexual intercourses. Knowledge concerning sexual health is vital for all particularly for adolescents, as they are vulnerable to adopt negative behaviors if not guided properly and at the right age.